Soft Computing Techniques in Vision Science - Patnaik,Srikanta; Yang,Yeon-Mo; SpringerLINK eBooks - English/International Collection (2012) (New York : Springer, 2012)
Annotation
Soft Computing Methods -- Review of Soft Computing Methods for Microwave and Millimeter-Wave Design -- Design of Microwave Filters Using Modified PSO -- Design of Microstrip Antennas and Other Components -- Design of a Nonlinear Taper Using SI Based Algorithms -- Multiobjective Optimizations for the Design of RF Windows.
Scholarly & Professional
Keywords: Soft computing; Computer vision; Engineering; Computational Intelligence; Image Processing and Computer Vision